2008
DOI: 10.3748/wjg.14.185
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and the metabolic syndrome: An update

Abstract: Sedentary lifestyle and poor dietary choices are leading to a weight gain epidemic in westernized countries, subsequently increasing the risk for developing the metabolic syndrome and nonalcoholic fatty liver disease (NAFLD). NAFLD is estimated to affect approximate 30% of the general US population and is considered the hepatic manifestation of the metabolic syndrome. Re c e n t f i n d i n g s l i n k i n g t h e c o m p o n e n t s o f t h e metabolic syndrome with NAFLD and the progression to nonalcoholic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
231
1
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(252 citation statements)
references
References 102 publications
4
231
1
12
Order By: Relevance
“…31 Therefore, it is noteworthy that MVPA for !250 minÁwk 21 led to a marked increase in the adiponectin levels in comparison with MVPA for <150 minÁwk 21 and MVPA for 150-250 minÁwk 21 (Table 4). Thus, MVPA for !250 minÁwk 21 is further beneficial as a lifestyle PA program in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…31 Therefore, it is noteworthy that MVPA for !250 minÁwk 21 led to a marked increase in the adiponectin levels in comparison with MVPA for <150 minÁwk 21 and MVPA for 150-250 minÁwk 21 (Table 4). Thus, MVPA for !250 minÁwk 21 is further beneficial as a lifestyle PA program in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is progressively diagnosed worldwide 25 , is tightly associated with obesity, type 2 diabetes, insulin-resistance and hypertension, and represents a severe risk for the development of cirrhosis and hepatocellular carcinoma 26 . Despite its severe drawbacks, liver biopsy is still the most common procedure for diagnosing NASH 18 .…”
mentioning
confidence: 99%
“…ER stress represents an important mechanism that underlies metabolic disorders (13)(14)(15), including the development of nonalcoholic fatty liver disease (NAFLD), a hallmark of metabolic syndrome and a major health burden in both developed and developing countries (16,17). A number of clinical studies have shown increased ER stress markers in both liver and adipose tissues from human subjects with obesity and NAFLD (18 -21).…”
mentioning
confidence: 99%